A study on damage mechanism modelling of shield tunnel under unloading based on damage–plasticity model of concrete. (May 2021) - Liu, Jianwen; Shi, Chenghua; Lei, Mingfeng; Wang, Zuxian; Cao, Chengyong; Lin, Yuexiang
Highlights: Previous studies are mostly carried out within the framework of elastic/plastic theory. A rational modelling procedure is proposed considering concrete damage. A novel bi–scalar damage constitutive model of concrete is developed. A elaborate numerical model is employed to simulate the tunnel–soil interaction. The damage and serviceability of shield tunnel under unloading are investigated. Abstract: Adjacent construction of soil excavations will adversely affect the service performance and optional safety of existing shield tunnels. Previous relevant studies on the excavation–induced responses of shield tunnel are mostly carried out within the framework of elastic or elastoplastic theory, despite the concrete inherent nonlinear damage mechanical characteristics such as strain softening, stiffness degradation, etc. Whereas damage or crack may inevitably occur when subjected to large deformations. Therefore, this paper presents a rational modelling procedure for the damage mechanism and serviceability of shield tunnel under unloading based on damage constitutive model of concrete, the nonlinear damage characteristics of concrete material are considered. First, a novel positive/negative decomposition strategy in energy norm is introduced herein to consider the asymmetric tensile/compressive material behavior of concrete, and a bi–scalar damage constitutive model is developed in turn. This damage constitutive model is then cast into the hybrid soil–tunnel numerical model that is constructed based on 3D nonlinear contact theory and the multiscale mixed modelling technology. Results show that when shield tunnel suffers unloading stress, tension damage dominates while compression damage is minor, additional shear force and bending moment are induced, the ovality of tunnel cross section and serviceability also vary along the tunnel longitudinal direction. The damage and degradation of concrete material will reduce the tunnel load–carrying capability and attenuate its ability to resist longitudinal heave and convergence deformation. Besides, the longitudinal coupling bolts on the tunnel upper part within the region between the two inflection points are prone to yield. It should be noted that, the segmental rings near the inflection point are most severely damaged, and exhibit the largest convergence deformation and lowest serviceability, where special attentions should be paid. It is demonstrated that the proposed modelling procedure is competent to capture the shield tunnel responses due to unloading.